2016
DOI: 10.1136/bcr-2016-217514
|View full text |Cite
|
Sign up to set email alerts
|

Transcervical approach to the removal of a deep-seated giant submandibular calculus and the submandibular gland

Abstract: Sialolithiasis is among the most common disease affecting the major salivary glands whereby the submandibular gland or its duct is affected in the majority of cases. We report a case of the surgical removal of a giant sialolith along with the submandibular gland using the transcervical approach and its clinical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Compared to other salivary glands, the sublingual gland is easier to remove. However, a detailed knowledge of the anatomy of the head and neck is required [18]. Because the lingual nerve is adjacent to Wharton's canal, damage to this nerve is a common complication of surgical removal of stones in sialolithiasis [19].…”
Section: Anatomy and Clinical Significance Of Sublingual Glandmentioning
confidence: 99%
“…Compared to other salivary glands, the sublingual gland is easier to remove. However, a detailed knowledge of the anatomy of the head and neck is required [18]. Because the lingual nerve is adjacent to Wharton's canal, damage to this nerve is a common complication of surgical removal of stones in sialolithiasis [19].…”
Section: Anatomy and Clinical Significance Of Sublingual Glandmentioning
confidence: 99%
“…[4][5] Stone size can vary from less than 1 mm (microsialolith) (Demidov and Ripolovska, 2019) to giant ones, reaching 3.5 cm (Goh et al, 2016), 3.7 cm (Omezli et al, 2016), or even 5.5 cm (megasialolith) (Raksin et al, 1975). [6][7][8][9] For example, the case published in 2019 revealed that number of sialoliths in the intraglandular duct system of the submandibular gland specimen can reach 8 stones (Demidov and Ripolovska, 2019). 6 A lot of basic imaging techniques (unenhanced computed tomography [CT], magnetic resonance imaging [MRI], different Х-ray, ultrasonography, sialoendoscopy, and different sialography imaging techniques) for sialolith detection are applied around the globe (Rzymska-Grala et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…[4][5] Stone size can vary from less than 1 mm (microsialolith) (Demidov and Ripolovska, 2019) to giant ones, reaching 3.5 cm (Goh et al, 2016), 3.7 cm (Omezli et al, 2016), or even 5.5 cm (megasialolith) (Raksin et al, 1975). [6][7][8][9] For example, the case published in 2019 revealed that number of sialoliths in the intraglandular duct system of the submandibular gland specimen can reach 8 stones (Demidov and Ripolovska, 2019). 6 A lot of basic imaging techniques (unenhanced computed tomography [CT], magnetic resonance imaging [MRI], different Х-ray, ultrasonography, sialoendoscopy, and different sialography imaging techniques) for sialolith detection are applied around the globe (Rzymska-Grala et al, 2010).…”
Section: Introductionmentioning
confidence: 99%